Pengaruh Kepemimpinan, Motivasi Dan Disiplin Kerja Terhadap Kinerja Karyawan PT. MPC Vetindo Pratama Makassar - Fitriani, Fitriani; Laekkeng, Mursalim; Kamidin, Masruhi; Mahmud, Amir (Universitas Pahlawan Tuanku Tambusai, 2024)
Abstract This study aims to determine the current performance conditions of PT. MPC Vetindo Pratama Makassar Employees.As for the variables used in this study are Leadership (X1), Motivation (X2), Work Discipline (X3) and performance (Y). For the sample in this study 64 respondents. The type of research used in this study is quantitative research using primary data. For the sampling technique in this study using the survey method. While for the analysis method used in this study, namely data validity test, data reliability test, normality test, multicollinearity test, heteroscedasticity test, multiple linear regression analysis, simultaneous influence test (F test), partial influence test (t) and simultaneous determination test R2. The research results show that: (1)Leadership has a positive and significant influence on employee performance at PT. MPC Vetindo Pratama Makassar. (2) Motivation has a positive and significant influence on employee performance at PT. MPC Vetindo Pratama Makassar. (3) Work discipline has a positive and significant influence on employee performance at PT. MPC Vetindo Pratama Makassar Keywords: Leadership, Motivation, Work Discipline, Employee Performance